Genetic ancestry and income are associated with dengue hemorrhagic fever in a highly admixed population - Blanton, Ronald E; Silva, Luciano K; Morato, Vanessa G; Parrado, Antonio R; Dias, Juarez P; Melo, Paulo R S; Reis, Eliana A G; Goddard, Katrina A B; Nunes, Márcio R T; Rodrigues, Sueli G; Vasconcelos, Pedro F C; Castro, Jesuina M; et al. (European journal of human genetics : EJHG, 2008)
To test whether African ancestry is protective for severe dengue, we genotyped 49 hospitalized cases of dengue hemorrhagic fever (DHF) as well as 293 neighborhood cases of dengue fever and 294 asymptomatic controls in Salvador, Bahia, Brazil. Ancestry-informative markers and 282 unlinked SNPs not associated with the clinical presentation of dengue were used to estimate ancestry. After controlling for income, both self-defined Afro-Brazilian ethnicity and African ancestry were protective for DHF ( P =0.02, OR=0.28 and P =0.02, OR=0.13, respectively). Income or an index of income indicators, however, was also independently associated with the diagnosis of DHF.